2011
DOI: 10.1149/2.033201jes
|View full text |Cite
|
Sign up to set email alerts
|

The Dry Etching Characteristics of HfAlO3Thin Films in CF4/Cl2/Ar Inductively Coupled Plasma

Abstract: In this study, the etching characteristics of HfAlO 3 thin film were investigated by varying the etch parameters such as the gas mixing ratio, the radio frequency power, the direct current bias voltage, and the process pressure in an inductively coupled plasma. The maximum etch rate of HfAlO 3 thin film and the selectivity of HfAlO 3 to SiO 2 were 20.55 nm/min and 0.38 in the CF 4 /Cl 2 /Ar (2:6:14 sccm) plasma, respectively. The plasma was analyzed by using optical emission spectroscopy. The chemical states o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Etching processes with a high etch rate, smooth surface, and highly anisotropic profiles are required to meet requirements of application for PCM cell fabrication. Previous reports demonstrate that Cl-based plasma is effectively applied for etching Albased alloy due to forming volatile AlCl 3 at high temperature (N 180°C ) or Al 2 Cl 6 at room temperature [5]. Although a high etch rate can be achieved by Cl-based plasma, the etching process is usually isotropic as a result of its chemical mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Etching processes with a high etch rate, smooth surface, and highly anisotropic profiles are required to meet requirements of application for PCM cell fabrication. Previous reports demonstrate that Cl-based plasma is effectively applied for etching Albased alloy due to forming volatile AlCl 3 at high temperature (N 180°C ) or Al 2 Cl 6 at room temperature [5]. Although a high etch rate can be achieved by Cl-based plasma, the etching process is usually isotropic as a result of its chemical mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…BCl 3 -based gas chemistry is widely used to etch metal oxide materials such as HfO 2 , Al 2 O 3 , Y 2 O 3 , and InSnO 3 because boron (B) acts as an oxygen scavenger, thus producing BOCl x volatile etch products. [15][16][17] There have been a few reports on dry etching of β-Ga 2 O 3 with various gas chemistry. [18][19][20][21][22] Hogan et al reported that inductively coupled plasma (ICP) etching with pure BCl 3 gas was effective to obtain etch rate of 43 nm min −1 at 400 W ICP and 100 W bias rf powers.…”
mentioning
confidence: 99%